PENGARUH PENERAPAN MANAJEMEN TERPADU, KOMPETENSI PROFESSIONAL GURU DAN PARTISIPASI ORANG TUA TERHADAP MUTU MTS SWASTA SE-BATANG TIMUR - Sri Sundari; Ngasbun Egar; Supriyono Purwosaputro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
School quality is one of the indicators of educational success, encompassing inputs, processes, and outputs. This study aims to analyse the influence of integrated quality management implementation, teachers' professional competence, and parental participation on the quality of private Madrasah Tsanawiyah in East Batang, both partially and simultaneously. The research employed a quantitative approach with a population of 246 individuals. A sample was selected using the Proportional Random Sampling technique based on Slovin's formula, resulting in 152 respondents. Data were collected through questionnaires and documentation, then analysed using descriptive statistics, prerequisite tests, and hypothesis testing through simple and multiple regression analyses, utilising SPSS version 26. The findings indicate that the implementation of integrated quality management positively and significantly influences school quality by 81.3% (Y = 1.077 + 0.040X1). Teachers' professional competence has a positive and significant influence of 82.3% (Y = 11.776 + 0.030X2), while parental participation contributes 83.3% (Y = 69.927 + 0.339X3). Simultaneously, integrated quality management, professional competence, and parental participation collectively have a significant positive influence of 88.8% on school quality (Y = 50.980 + 0.190X1 + 0.295X2 + 0.356X3). These findings highlight the importance of integrating quality management, enhancing teachers' competencies, and involving parents in improving the quality of education at private Madrasah Tsanawiyah in East Batang.